Identifying Student Motivation for Learning Islamic Education in Indonesian Senior High Schools - Japeri, Japeri; Rahmi, Elvi; Izmi, Nelly; Irayanti, Irma; Eki Saputri, Teni (Ahlussunnah: Journal of Islamic Education, 2023)
Understanding student motivation for learning Islamic education in Indonesian senior high schools is crucial for enhancing educational outcomes and student engagement. The aim of this research is to look at students' intrinsic motivation, students' extrinsic motivation, supporting and inhibiting factors in learning Islamic religious education. This research uses descriptive qualitative methods. The data collection techniques used are observation, interviews, and documentation with data analysis through data reduction, data presentation, and drawing conclusions and verification. The results of this research were obtained: i) the intrinsic motivation of students at Senior High School in learning Islamic religious education was obtained through the appreciation given by the teacher and the students' sense of responsibility. This award is motivation for students to develop and progress further in their learning process, ii) extrinsic motivation for Senior High School students is obtained from the motivation provided by teachers, principals, and all the environment in the school. Adequate infrastructure is one of the motivations for student learning in achieving goals, iii) supporting factors in increasing student learning motivation in learning Islamic religious education, namely students are given Islamic religious learning guidance, in the form of congregational prayers, tahfiz, reading the Quran and delivering learning material. The inhibiting factor in increasing students' learning motivation in learning Islamic religious education is the lack of Islamic religious education lesson hours at school. Apart from the lack of teaching hours for Islamic religious education teachers, students who study religion are less aware of the importance of studying Islam. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.